Embrace your brokenness: a narrative journey of an immigrant - Monem, Nikoo, author; Bates, Haley, advisor; Aoki, Eric, committee member; Emami, Sanam, committee member; Lehene, Marius, committee member (Colorado State University. Libraries, 2024)
"Embrace Your Brokenness" unfolds the symbolic narrative of my immigrant journey through a collection of works, capturing the intricate complexities of identity and resilience. The artworks delve into themes of connection, border blending, and the interplay between external presentation and internal reality within the context of my own life. This thesis explores the unity and dissonance inherent in my personal experience, delving into the transient nature of memories and the emotional intricacies they hold. The signature of this collection are the delicate rose pattern porcelain pieces which serve as reflections of my roots and connections to my homeland, evoking a profound sense of belonging and contributing to my self-portrait within this collection. Utilizing visual narratives, each piece becomes a nuanced story, framing my daily struggles with adapting to a new life in the United States. Aligned with a broader theme of unity, "Embrace Your Brokenness" unveils the complexities of the immigrant experience, offering a tangible representation of the often-unseen challenges I have faced as both an immigrant and an artist. Through this body of work, viewers are invited to contemplate the concealed stories and connections that contribute to the collective human experience.
Keywords: immigration studies; photography; crafts; visual arts; jewelry